Ceramium cornutum and Ceramium pallidum (Rhodophyta: Ceramiales) two new records for Morocco: morphology and reproductive structures. Issue 1 (2nd January 2016) - Hassoun, Mustapha; Salhi, Ghizlane; Moussa, Hanaa; Riadi, Hassane; Kazzaz, Mohamed; Zbakh, Hanaa
Abstract: Two macroalgal taxa are reported for the first time from Morocco: Ceramium cornutum and Ceramium pallidum (Ceramiaceae: Ceramiales). The last species is also reported for the first time from Africa. Specimens of both taxa were collected in the lower intertidal to subtidal zones from different localities in northwest Morocco. These new records, are examined in detail and compared with congeners such as Ceramium cimbricum, Ceramium diaphanum, Ceramium tenerrimum and Ceramium virgatum . Both morphological features and reproductive structures are given; illustrations, habitat, geographic distribution and taxonomic remarks for each species are also provided. In this paper new data are provided for C . cornutum, especially number of periaxial cells and type of rhizoids.